Cholelithiasis in children - E. M. Halimun; Hermien W. Moeryono (Indonesian Pediatric Society, 1984)
Gallstone disease is very rare in children. This communication is a report on three cases of cholelithiasis in children found in the last four years in Harapan Kita Hospital, Jakarta. They were all girls of ll. 5 and 9 y ears old respectively. The etiologic factors were Salmonellosis, Congenital stenosis of the distal end of CBD and Thalassemia. All patients were survive and well after surgical treatment. Ultrasonography gives a big contribution in diagnosing an acquired obstruction of the extra hepatic biliary system.